The problem of the incidence of falls in hospitals in Poland in the opinion of physiotherapists - Marcin Mikos; Agnieszka Ciukszo; Marta Podhorecka; Mateusz Curyło (Journal of Education, Health and Sport, 2023)
Introduction: An unintentional fall is an event whereby a person inadvertently comes to rest on the ground or floor for reasons other than a violent impact, loss of consciousness, or the sudden onset of paralysis that can occur during a stroke or epileptic seizure. Implementing effective strategies can reduce the risk of falls, reduce fall-related injuries and reduce healthcare costs. Aim: The aim of the study was to get to know the opinion of physiotherapists working in one of the Krakow multi-specialty hospitals on the risk of falls in hospitals in Poland.